Knowledge, attitude, and practice of hospice care among senior nursing staff in Chongqing and Hebei: a cross-regional study - Huan Liu; Ying Zeng; Qin Chen; Jihua Feng; Lu Wang (Frontiers in Public Health)
BackgroundThe demand for quality hospice care rises in China as the population ages. Specialized gerontological advanced practice nurses (GAPNs) are vital to the Chinese healthcare system, yet their knowledge, attitudes, and practices (KAP) regarding hospice care in China remain poorly understood.ObjectivesTo explore the KAP toward hospice care in specialized GAPNs and the factors influencing KAP.MethodsThis cross-sectional study was conducted from May 6, 2023, to July 30, 2023, in GAPNs working in Chongqing and Hebei. This study used a previously developed scale on the KAP toward hospice care. Descriptive analysis, univariable and multivariable regression analyses, and correlation analyses were used.ResultsA total of 300 valid questionnaires were collected. The median knowledge score was 7. The median attitude score was 82. The proportion of participants with hospice care experience was 15.7%. The median confidence in practice score was 38. The median actual practice score was 40. High school/vocational school education and unwillingness to participate in hospice care were negatively associated with knowledge. Unwillingness to participate in hospice care and knowledge scores were positively associated with attitudes. Age 41–50 and attitude scores were positively associated with confidence in practice, while never provided hospice care and Hebei province were negatively associated.ConclusionGAPNs in Chongqing and Hebei show moderate KAP toward hospice care, with Chongqing performing better. The regional differences found suggest the need for region-specific education and policy interventions.